Biological-chemical treatment of polycyclic aromatic hydrocarbon contaminated soil / Salina Alias - Alias, Salina (2016)
Industrialization has caused a great deal of environmental pollutions such as soil contamination via deposition and spillage of contaminants. One of the major contaminants is high molecular weight (HMW) polycyclic aromatic hydrocarbon (PAH), specifically the benzo(a)pyrene. Benzo(a)pyrene is known for its carcinogenic effect. Several soil remediation strategies have been proposed. However, to date, remediation of benzo(a)pyrene contaminated soil using zero-valent iron (ZVI) and hybrid bacteria-ZVI has not been investigated. The capability of bacteria, namely, Corynebacterium urealyticum and Sphingobacterium spiritovorum to degrade benzo(a)pyrene in soil were firstly investigated in three conditions, single, binary and ternary substrate experiments. Binary and ternary substrate experiments involved the degradation of benzo(a)pyrene, a HMW-PAH with the presence of low molecular weight (LMW) PAH. It was found that both bacteria were capable of degrading the benzo(a)pyrene in the presence of anthracene and phenanthrene (both are LMW-PAHs). However the degree of degradation varied. For instance, the degradation of benzo(a)pyrene was enhanced with the presence of anthracene and phenanthrene in ternary substrate experiment, where 30% of benzo(a)pyrene was degraded. In the single and binary substrate experiment which only phenanthrene was present, about 24% and 14% of benzo(a)pyrene was degraded. Both bacteria degraded the benzo(a)pyrene at the rate of 1.508 - 3.229 mg/kg/day. Then, the ability of ZVI, an engineered iron particles to facilitate in the oxidation of benzo(a)pyrene, was evaluated in single and mixed PAHs experiments with different ZVI concentrations. In this case, it was found that the higher the dosage of ZVI in the soil, the more benzo(a)pyrene was oxidized. The degradation rates for ZVI oxidation were at 0.154 - 0.718 mg/kg/minutes which is 150 times higher than the biological treatment. The soil contaminated by benzo(a)pyrene was then sequentially and simultaneously remediated with bacteria and ZVI in hybrid treatment approaches. A slight enhancement in the removal of benzo(a)pyrene was found in the hybrid treatment compared to the individual treatment approach. However, the most effective hybrid approach was through the sequence treatment with bacteria {Sphingobacterium spiritovorum) followed by ZVI. In this, 48% of benzo(a)pyrene was removed. The maximum biotic and abiotic conditions for the efficient remediation strategy of benzo(a)pyrene were also investigated. It was found that concentration of bacteria at CFU 108/g, temperature 35°C and pH 4 were the maximum conditions for the hybrid bacteria-ZVI. Mathematical models to predict benzo(a)pyrene removal using S. spiritovorum-biologicdiX treatment, ZVI-chemical treatment and hybrid S. spiritovorum-ZVl were successfully developed and validated in this study. The proposed models were able to provide prediction of benzo(a)pyrene removal that will help engineers to plan and design the remediation strategy in order to minimize the impact of PAH contamination on human and environment.